Perbandingan profil lipid dengan hipertensi pada diabetes mellitus tipe 2 dengan atau tanpa hipertensi di RS H. Adam Malik, Medan, Indonesia - Jelita Siregar (Intisari Sains Medis, 2019)
Background: Atherosclerosis is a complex process. It involve many pathological event including endotelial dysfunction, abnormal lipid metabolism, trombosit activation, trombosis, oxidative stres, activation smooth muscle in blood vessel. Recently, it is known that inflamation plays a role in every steps of atherosklerosis formation. Diabetes Mellitus (DM) is the main risk factor of cardiovascular disease. The epidemiology showed that cardiovasculer mortality 2 to 3 times higher compared to population without DM. This study aims to know the difference in lipid profile between type 2 diabetics’ patients with and without hypertension.Method: This is a cross sectional study, which was held in Patology Clinic Department FK-USU / H. Adam Malik Hospital, from Agustus 2017 to November 2017. Target population is type-2 DM. Data were analyzed using SPSS version 17 for windows.Result: It found 72 subject is 36 people as patient DM type 2 with hypertension and 36 people as control. According to statistic analysis found significant difference between total cholesterol, triglyceride, HDL and LDL in patients with DM type 2 and hypertension compared with patients with DM type 2 without hypertension (p < 0,05).Conclusion: In this study we found there are significant positive increased level of total cholesterol, trigliseride, HDL and LDL and hypertension on type-2 DM population.